P197 Down with the kids – are we doing enough to provide a holistic sexual health service to vulnerableyoung people?. (18th May 2015) - Currie, Susanna; Houldey, Annie; Ward, Chris; Lee, Vincent
Abstract : Background/introduction: The sexual health of young people in the UK is amongst the worst in Europe, with high prevalence of sexually transmitted infections (STIs) and unwanted pregnancies. Although most are involved in consensual sexual activity, they may also be victims of sexual abuse or exploitation, usually unrecognised by themselves or health care professionals. We have developed a proforma based on the BASHH young persons' proforma for patients under 18 attending the service which includes safe guarding issues. Aim(s)/objectives: To review the management of young persons' sexual health in an inner city sexual health clinic. Methods: Retrospective case note review of all patients <18 years attending clinic in 2012 and 2013. Results: 93 patients were identified; 34 (36.6%) were <16 years (7 M; 27F); median age 15 years (range 11–15). 32 (94.1%) were sexually active; all (100%) of which accepted STI screening. 14 (45.2%) tested positive for at least one STI. The proforma was completed for 33 (97.1%) patients. 14 (41.2%) of the patients had contact with social services; 10 (29.4%) had non-consensual sexual activity; 15 (44.1%) had mental health issues and 4 (11.8%) used recreational drugs. All of them have been followed up according to local guidelines. Conclusion: The proforma enables us to identify those with safeguarding issues and STIs. An appropriate safeguarding referral pathway and local multi-agency arrangements are in place to help and protect these young people. Further education and communication are needed to raise the awareness and improve the sexual health and wellbeing of the young people.